MRI Evaluation in Acute Spinal Trauma in Tertiary Center of Nepal - Acharya, Rajesh; Kumar Chhetri , Pramod; Natraj Prasad, V.; Thapa, Kripesh; Mishra, Manish; Ghimire , Arati (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Spine injury is one of the leading caused for disability in Nepal. Patients with trauma related spine injury leads to neurological dysfunction, focal deficits and even fatal life threating events. The timely intervention in acute spinal trauma injury could save the patients from disability and mortality risk. Imaging modalities like Xray, CT Scan and MRI helps in diagnosis and management of spinal trauma. MRI plays crucial role in detection of spinal cord and soft tissue injuries. It is superior than CT scan in evaluation of spinal cord injuries, ligament, soft issue structures, disc, and occult osseous injuries. The objective of this research is to evaluate MRI in acute spinal trauma in tertiary center of Nepal. Methods This is descriptive hospital based observational study in those patients who were admitted and referred in hospital for MRI with acute spinal trauma injury. Data were analysed by SPSS 2022. Results Acute spinal trauma is most common in male with ratio of 1.7 with the mean±SD of age was found to be 50.98±19.26 years. Most common mode of injury were fall injury (76%). Most common spinal region involved were lumbar (42%) followed by thoracic (36%), dorso-lumbar (14%) and cervical (8%) region respectively. Spinal cord contusion with edema, disc rupture, paravertebral collection and ligament injury were seen. Most common type of fractures were simple compression fracture (72%), followed by burst fracture (16%), both (6%) and listhesis and sub/dislocations (6%). Spinal cord injury were seen in 22%, followed by disc rupture, paravertebral collection and ligament injury. Conclusions MRI helps in evaluating vertebrae, spinal cord, ligament and disc injuries. We can assess the cord contusion, edema and canal compression. It provides involvement, extension and severity of cord injury. It endowed about outcome of surgery as well as conservative management in patient of spinal injury.